ChemInform Abstract: Chemo‐ and Regioselective Reductive Deoxygenation of 1‐En‐4‐yn‐ols into 1, 4‐Enynes Through FeF3 and TfOH Co‐Catalysis. Issue 35 (August 2016) - Yang, Zonglian; Kumar, Rapolu Kiran; Liao, Peiqiu; Liu, Zhaohong; Li, Xingqi; Bi, Xihe
Abstract: The reductive deoxygenation of enynols (III) with 2‐nitrobenzenesulfonic acid hydrazide leads to desired 1, 4‐enynes (IV).